Pelestarian Lembaga Perkawinan: Upaya Mencegah Dampak Ekonomi Krisis Seks dan Depopulasi Akibat Praktik Childfree, Waithood, dan Freesex di Indonesia - Gusli, Tan (JURNAL ILMIAH GEMA PERENCANA, 2024)
This policy paper explains that Indonesia as a country supported by religious culture and family spirit does not guarantee freedom from the threat of sexual recession. Currently, there is a movement to postpone marriage (waithood) and be reluctant to have children (childfree) which is widely carried out by the millennial generation, even the practice of free sex has hit students in Indonesia. This study will discuss the practices of Childfree, Waithood, and Freesex in relation to the alleged crisis of trust in the institution of marriage. The approach method used is descriptive qualitative through literature studies. Data shows that there has been a decrease in the number of marriages, an increase in divorce cases, and a decrease in the birth rate in Indonesia. The economic impacts that are feared to arise afterwards are the sex crisis and depopulation as has happened in Japan. Not only that, the case of depopulation in Japan shows a domino effect on asset dysfunction. Policy recommendations to overcome this are to include the Sex Education and Sakinah Family curriculum at all levels of education. Adding the Sakinah Family Online Service feature in the "Pusaka Kemenag Super Apps" and synergizing the Ministry of Religion's services at the Public Service Mall (MPP).